The role of biologically active substances in the development of the pathological process of Pseudomonas syringae pv. atrofaciens - Pasichnyk, Lidiia; Huliaieva, Hanna; Patyka , Mykola (Problems of Environmental Biotechnology, 2021)
Investigation of the influence of biologically active substances, including those created with the help of nanotechnologies, on the intensity of the development of the pathological process caused by P. syringae pv. Atrofaciens on spring wheat of the Pecheryanka variety.